Expression of paralogous SEP-, FUL-, AG- and STK-like MADS-box genes in wild-type and peloric Phalaenopsis flowers - Acri-Nunes-Miranda, Roberta; Mondragón Palomino, Mariana (Frontiers in Plant Science, 2014)
The diverse flowers of Orchidaceae are the result of several major morphological transitions, among them the most studied is the differentiation of the inner median tepal into the labellum, a perianth organ key in pollinator attraction. Type A peloria lacking stamens and with ectopic labella in place of inner lateral tepals are useful for testing models on the genes specifying these organs by comparing their patterns of expression between wild-type and peloric flowers. Previous studies focused on DEFICIENS and GLOBOSA-like MADS-box genes because of their conserved role in perianth and stamen development. The ‘orchid code’ model summarizes this work and shows in Orchidaceae there are four paralogous lineages of DEFICIENS/AP3-like genes differentially expressed in each floral whorl. Experimental tests of this model showed the conserved, higher expression of genes from two specific DEF-like gene lineages is associated with labellum development. The present study tests whether eight MADS-box candidate SEP-, FUL-, AG- and STK-like genes have been specifically duplicated in the Orchidaceae and are also differentially expressed in association with the distinct flower organs of Phalaenopsis hyb. “Athens”. The gene trees indicate orchid-specific duplications. In a way analogous to what is observed in labellum-specific DEF-like genes, a two-fold increase in the expression of SEP3-like gene PhaMADS7 was measured in the labellum-like inner lateral tepals of peloric flowers. The overlap between SEP3-like and DEF-like genes suggests both are associated with labellum specification and similar positional cues determine their domains of expression. In contrast, the uniform messenger levels of FUL-like genes suggest they are involved in the development of all organs and their expression in the ovary suggests cell differentiation starts before pollination. As previously reported AG-like and STK-like are exclusively expressed in gynostemium and ovary, however no evidence for tran